Development of Training Profession Practices for our Teachers to Increase Pedagogic Competence - Sangadji, Kapraja; Ibrahim, Nurdin; Solihatin, Etin; Jarudin (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of developing this training material is to facilitate teacher tutors to fully understand the concept of teacher professional practice, as well as to hone their knowledge, attitudes, and skills, as well as guiding procedures for tutor teachers in improving pedagogical competencies of undergraduate students in managing quality learning. The development of training materials for tutor teachers in the form of modules refers to the Rowntree and Brog and Gall models. The Rowntree model is a development model specifically aimed at developing learning materials that have three main stages, namely planning materials, preparing for writing, and writing and rewriting. While the Brog and Gall model uses the first step, preliminary research. The training material can have a positive influence and have a significant impact on tutors effectively mentoring students practice. This will be seen from the increase in pedagogical competence of students practicing in managing learning that results from mentoring teacher tutoring activities after using training modules. Pedagogic competence can improve learning performance and contribute to the ability and willingness in pedagogic collaboration for self-development and contribute to the development of students being taught.